Radicalization through social networks during the pandemic - Frățilă, Cătălina (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The coronavirus pandemic has led to the use of social networks at an unprecedented level. The use of social networks and isolation have created an ideal framework for carrying out radicalization activities. Social networks have helped with the way communication is achieved, but there are also negative effects produced by them, and online radicalization is one of these negative effects. In the digital age, information has crossed the barriers imposed by time and geographical space. This was also exploited by terrorist groups that took advantage of the opportunities offered by the online environment, and the pandemic period represented a new opportunity for these groups to recruit new members. Based on this premise, we analyzed the articles on radicalization through social networks to observe the effects that the coronavirus pandemic had on the research of the phenomenon of radicalization. We believe that in this digital age, efficient communication is difficult to achieve, given the large volume of information accessible to all. That is why researchers in the field of radicalization have an extremely high responsibility, namely, the efficient spread of messages in order to prevent this phenomenon.